EXIST, RESIST, DEMAND! ASPECTS OF THE HISTORICAL-IDEOLOGICAL CONSTRUCTION OF BRAZILIAN RACISM AND THE PLACE OF THE BLACK MOVEMENT IN THE FIGHT FOR THEIR DESCONSTRUCTION - Barros, Bárbara Sepúlveda; Martins, Luci Helena [UNESP] (Associacao Pro-Ensino Superior em Novo Hamburgo, 2019)
The work in question seeks to recover, from a bibliographical research, the main historical determinants of racism in Brazil, showing the impact between us, the theories that developed in Europe between the XVIII and XIX centuries. Such theories promoted a hierarchy of human groups, from the physical and biological characters, attesting to the superiority of the Caucasian, Caucasian or Aryan race, and to the inferiorities of the others. This research aims to demonstrate how, in the Brazilian context, this diagnosis implied a non-inclusion of blacks in the citizen category, even in post-abolition, when the ideals of freedom and equality brought about by liberalism end up being filtered by the local elites, the entire population. Ideologies such as money laundering and racial democracy are carried out by the state, widening its marginalization. It also presents the process of mobilization and maturation of the Black Brazilian Movement, from which a change can be seen, above all by the conquest of affirmative actions in the 2000s.
EXISTIR, RESISTIR, EXIGIR! ASPECTOS DA CONSTRUÇÃO HISTÓRICO-IDEOLÓGICA DO RACISMO BRASILEIRO E O LUGAR DO MOVIMENTO NEGRO NA LUTA A FAVOR DA SUA DESCONSTRUÇÃO
Keywords: Brazilian black movement; Racial issues; Racism